Analysis of Factors Affecting the Weaning of Mechanical Ventilation at ICU RSUD Prof.Dr.Margono Soekarjo Purwokerto - Etika Emaliyawati; Esti Dwi Anani; Ayu Prawesti (Padjadjaran Acute Care Nursing Journal, 2019)
The weaning of mechanical ventilation is a complex process and depends on many factors. The failure to wean mechanical ventilation may lead to prolonged duration of mechanical ventilation, which may increase the risk of ventilator associated pneumonia (VAP), morbidity, mortality, increased hospital costs and lower quality of hospital services. In the year 2016, in ICU RSUD Prof.Dr.Margono Soekarjo Purwokerto, in average there is a 20% failure of mechanical ventilation, if not followed up will adversely affect the patient. Factors investigated in this study included patient, nurses, collaboration and organization. The purpose of this study is to analyze the factors that affect implementation of the weaning of mechanical ventilation in ICU Room Prof.Dr.Margono Soekarjo General Hospital Purwokerto.The method used in this research was descriptive quantitative analytic design with cross sectional approach on 47 mechanical ventilation weaning activities. The sample selection was conducted by accidental sampling technique. Measurements for nurses were carried out using validated values including knowledge, experience and collaboration. While the observation sheet included the implementation of standard operating procedures for mechanical ventilation weaning, collaboration, patients APACHE II score and weaning results.The result of bivariate test showed that there were influence of patient (0.000), nurse (0,021), collaboration (0,024) and organization (0,011) to mechanical ventilation weaning activity. The result of logistic regression test showed that the patient was the most influential factor on mechanical ventilation weaning activity with 87% probability.Nurses should pay more attention to patients especially with high APACHE II scores (≥20) because of the risk of mechanical ventilation weaning failure. Assessment of weaning readiness must be carried out daily with appropriate assessment. While hospitals need to revise policies on mechanical ventilation weaning procedure and continue education and training programme related to patients criticality and collaboration.